Metal–Organic Framework-Assisted Synthesis of Compact Fe2O3 Nanotubes in Co3O4 Host with Enhanced Lithium Storage Properties - Zhang, Song Lin; Guan, Bu Yuan; Wu, Hao Bin; Lou, Xiong Wen David (Nano-Micro Letters, 2018)
Transition metal oxides are promising candidates for the high-capacity anode material in lithium-ion batteries. The electrochemical performance of transition metal oxides can be improved by constructing suitable composite architectures. Herein, we demonstrate a metal–organic framework (MOF)-assisted strategy for the synthesis of a hierarchical hybrid nanostructure composed of Fe2O3 nanotubes assembled in Co3O4 host. Starting from MOF composite precursors (Fe-based MOF encapsulated in a Co-based host matrix), a complex structure of Co3O4 host and engulfed Fe2O3 nanotubes was prepared by a simple annealing treatment in air. By virtue of their structural and compositional features, these hierarchical composite particles reveal enhanced lithium storage properties when employed as anodes for lithium-ion batteries. Highlights: 1 A metal–organic framework (MOF)-assisted approach is developed for the synthesis of hierarchical composite particles composed of Fe2O3 nanotubes encapsulated in a Co3O4 host matrix. 2 The hierarchical Fe2O3 nanotubes@Co3O4 composite particles exhibit excellent electrochemical performance when evaluated as an anode material for lithium-ion batteries (LIBs).